2011
DOI: 10.1007/s12010-011-9344-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Identification of a Chymotryptic Hydrolysate of Alpha-Lactalbumin Stimulating Cholecystokinin Release in STC-1 Cells

Abstract: Alpha-lactalbumin hydrolysate is of significant interest, due to its potential application as a source of bioactive peptides in nutraceutical and pharmaceutical domains. This study was focused on the cholecystokinin (CCK) family compounds which are small peptides involved in the satiety control. The action of chymotryptic hydrolysate of alpha-lactalbumin on cholecystokinin release from intestinal endocrine STC-1 cells was investigated. We demonstrated for the first time that a chymotryptic hydrolysate of alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It has been suggested that the receptor of GLF might be common to that of complement C1q [30]. Peptides stimulating the release of cholecystokinin have been reported to be released from -lactalbumin [31].…”
Section: -Lactalbuminmentioning
confidence: 99%
“…It has been suggested that the receptor of GLF might be common to that of complement C1q [30]. Peptides stimulating the release of cholecystokinin have been reported to be released from -lactalbumin [31].…”
Section: -Lactalbuminmentioning
confidence: 99%
“…In recent years, this hybrid technique has also been used for the fast identification of natural peptides. [13][14][15][16][17] To investigate the chemical biodiversity of biologically active cyclic hexapeptides in the metabolites from microorganism, we reported here the identification of pyrroloindoline-containing cyclic hexapeptides in the fermentation broth of S. alboflavus 313 by HPLC-diode array detector (DAD)-ESI-MS/MS. All NW-series cyclic hexapeptides consist of N-methylalanine (or alanine), valine (or leucine), chlorinated (or non-chlorinated) tryptophan derivative (Trp) and three piperazic acids (Pas; or its derivatives), their structures are shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%